Forensic mental health assessment in Latin-America: A survey on current practices - Arbach, Karin (2024)
A survey was conducted online, reaching 191 psychologists across 10 Latin-American countries. Questions explored professional practices in ﬁve areas of forensic mental health assessment: mental state at the time of the offense, risk for violence, risk for sexual violence, malingering and psychological injury. The primary distinction observed was the prevalence of projective tests and Rorschach use in southern countries, contrasted with a preference for systematized tests like multiscale personality inventories and clinical assessment scales in Central American nations. We identiﬁed a minimal utilization of speciﬁc forensic tools. Some possible explanations are discussed.